Corporalidades De Meninas E Meninos Na Educação Infantil: Normatividades E (Re)Significações De Gênero - Inoue, Laura Tereza De Sa E Benevides [UNIFESP] (2018)
This Master's Research Aims To Understand The Process Of Social Construction Of The Bodies Of Girls And Boys In Child Education, Seeking To Identify Gender Norms And The Ways That Children (Re)Signify Them. It Was Based On An Ethnographic Study With Five-Years Old Children In A Municipal School Of Early Childhood Education In The City Of São Paulo (Emei). How Does The "Being A Girl" And "Being A Boy" Marks The Corporalities Of Children In Early Childhood Education? How Do Girls And Boys Express Gender Normativities In Their Bodies And How Do They Resignify Them? The Research Has The Sociology Of The Childhood, Studies Of Gender, Feminist Studies And Studies Of The Body As The Theoretical Reference. The Research Outcome Reveals That The Gender Norms Present In The Corporalities Of Girls And Boys, Reflected In The Forms Of Clothing, Adornments, Toys And Fantasies Marked By The Socially Established Expectations Of Femininity And Masculinity. It Shows How Small Children, Through Play And Movements, Experience The